Malignancy in a retrospective cohort of 17 patients with Dermatomyositis or Polymyositis in southern Tunisia - Sellami Khadija; Mseddi Madiha; Snoussi Mouna; Gharbi Hela; Frikha Faten; Salah Rayda Ben; Jallouli Moez; Marzouk Sameh; Masmoudi Abderrahmen; Bahloul Zouhir; Turki Hamida (Sciendo, 2018)
Introduction. The prognosis of dermatomyositis (DM)/ polymyositis (PM) in adults is partly related to their association with neoplasia. The aim of our study was to report the epidemiologic, clinical, paraclinical, therapeutic and evolutionary aspects of DM associated with malignancy in patients from Sfax, south eastern of Tunisia. Methods. A retrospective cohort study of patients with DM or PM admitted in Dermatology and Internal Medicine Departments of Hedi Chaker University Hospital of Sfax between 1996 and 2015. Cases of DM or PM associated with malignancy were retained. Results. Seventeen cases (13.5%) of DM or PM associated with malignancy were noted. Fourteen patients had DM and 3 patients had PM. The Sex ratio M / F was 0.3 and the mean age at diagnosis was 56.5 years. In DM patients, malignancy preceded the myositis in 64.2% of cases. In PM patients, only one patient was known to have breast cancer and the myositis revealed the cancer for 2 others. Treatment consisted of corticosteroids associated with methotrexate in 4 cases. Outcome was fatal in 5 cases (29.4%), due to the underlying cancer in 3 cases. Swallowing disorders related to DM/PM were responsible for death in 2 cases. Conclusion. There are no specific clinical or biological features in paraneoplastic DM. In our series, breast neoplasm represented the first cancer associated with DM. Cancers of nasopharynx, colon and urinary tract had the second position.